A 2.5D spectral approach to represent acoustic and elastic waveguides interaction on thin slab structures. (2017) - Cruz-Muñoz, FJ.; Romero, A.; Tadeu, A.; Galvín, P.
Abstract: In this paper, we propose a spectral element method (SEM) to study guided waves in coupled problems involving thin-walled structures and fluid-acoustic cavities. The numerical method is based on the subdomain decomposition of the fluid-structure system. Two spectral elements are developed to represent the fluid and the structure. A plate element based on a mixed Reissner-Mindlin and Kirchhoff-Love formulation is proposed to represent the thin-walled structure. This element uses C0 approximation functions to overcome the difficulties to formulate elements with arbitrary order from C 1 functions. The proposed element uses a substitute transverse shear strain field resulting free shear locking. The fluid element is derived from the Helmholtz equation. These elements use Lagrange polynomials as shape functions at the Legendre-Gauss-Lobatto (LGL) points. The analysis is carried out by a two-and-a-half dimension (2.5D) approach in the wavenumber-frequency domain. The guided wave in a fluid cavity with a flexible side is analysed.